The Value of Corporate Philanthropy During Times of Crisis: The Sensegiving Effect of Employee Involvement - Muller, Alan; Kräussl, Roman 1970- (2011)
Recent research suggests that philanthropy’s value to the firm is largely mediated by contextual factors such as managers’ assumed motives for charity. Our article extends this contingency perspective using a “sensegiving” lens, by which external actors’ interpretations of organizational actions may be influenced by the way in which the organization communicates about those actions. We consider how sensegiving features in philanthropy-related press releases affect whether investors value those donation decisions. For the empirical investigation in this study, we analyze abnormal returns to announcements by U.S. Fortune 500 firms documenting their donations to Hurricane Katrina disaster relief in 2005. We expect that in general, donation decisions would be controversial given the uncertainty surrounding the hurricane’s economic effects at the time. However, we also propose that announcements emphasizing employee involvement in the donation send investors positive signals about the firm’s ability to bounce back from the disaster’s adverse effects. We find empirical support for the proposed hypotheses, and discuss the implications for theory and practice.
Keywords: sensegiving; Hurricane Katrina; Firm value; Employee involvement; Corporate Philanthropy